2019
DOI: 10.24191/jibe.v4i1.14414
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationship Marketing Tactics & Customer Loyalty: Issues in the Malaysian Mobile Telecommunication Sector

Abstract: Most of today’s business firms are facing numerous challenges in sustaining customer loyalty due to a ferocious competitive environment. This study explores issues on relationship marketing and customer loyalty within the mobile telecommunications sector. In-depth interviews with targeted respondents were conducted to understand their initial perceptions on relationship marketing tactics issues and its influence on customer loyalty. Specifically, the study aims to acquire deeper insights into the motivational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Users of telecommunications networks acquire a fondness for their brands, think about their brands, and show loyalty behaviours and intentions toward their brands through satisfaction with these networks. The positive relationship between consumer satisfaction and consumer loyalty is supported in the studies on the consumer loyalty (Dewi et al, 2021;Sudari et al, 2019;Yeohan, 2019), and on other service industries (Hasfar et al, 2020;Putit & Abdullah, 2019;Syahputra & Murwatiningsih, 2019;Wulur, Militina & Achmad, 2020).…”
Section: Interpretation and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Users of telecommunications networks acquire a fondness for their brands, think about their brands, and show loyalty behaviours and intentions toward their brands through satisfaction with these networks. The positive relationship between consumer satisfaction and consumer loyalty is supported in the studies on the consumer loyalty (Dewi et al, 2021;Sudari et al, 2019;Yeohan, 2019), and on other service industries (Hasfar et al, 2020;Putit & Abdullah, 2019;Syahputra & Murwatiningsih, 2019;Wulur, Militina & Achmad, 2020).…”
Section: Interpretation and Discussionmentioning
confidence: 88%
“…According to Dewi et al, (2021), there was a positive correlation between the two ideas, with an improvement in customer satisfaction likely leading to an increase in customer loyalty. When Putit and Abdullah (2019) conducted research on Malaysia's telecommunications industry, they found that customer satisfaction can mediate between (value, service quality, positive brand image, price perception and switching cost) on the one hand as well as customer loyalty among Swedish mobile telecommunication subscribers on the other. Overall, consumers satisfaction and loyalty were found to be directly correlated.…”
Section: Relationship Between Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%